Miliç Irmağı (Terme, Samsun) Balık Faunası - Uğurlu, Selma; Polat, Nazmi (My University, 2006)
The research done by aiming to find out the fish species inhabiting in the river Miliç took place between April 2004 and July 2005. Seven stations all representing the ecological characters of the stream were determined for fish collection along the stream. Totally 286 fish samples were caught by electroshocker, fishing nets, fishing cast net and fishing lines during the study time. In this study 16 species belonging to 5 families (Cyprinidae, Mugilidae, Syngnathidae, Blenniidae, Gobiidae) were identified.

The research done by aiming to find out the fish species inhabiting in the river Miliç took place between April 2004 and July 2005. Seven stations all representing the ecological characters of the stream were determined for fish collection along the stream. Totally 286 fish samples were caught by electroshocker, fishing nets, fishing cast net and fishing lines during the study time. In this study 16 species belonging to 5 families (Cyprinidae, Mugilidae, Syngnathidae, Blenniidae, Gobiidae) were identified.
Fish fauna of the River Miliç (Terme, Samsun)
Keywords: Balıkçılık; Zooloji